Association Between Esophagitis Severity and GERDQ Score, Sleep, Life Quality among GERD Patients - Waleleng, Andrew; Richard, Timoteus; Rombot, Tisa; Waleleng, Bradley Jimmy; Wenas, Nelly (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Gastroesophageal reflux disease (GERD) is characterized with acid reflux, therefore may lead to esophagitis. Acid reflux may cause night symptom of GERD, therefore resulting in decreased sleep and life quality. Gastroesophageal reflux disease questionnaire (GERDQ) is a simple and validated questionnaire for diagnosing GERD. This article aims to investigate association between esophagitis severity and GERDQ score, sleep, life quality among GERD patients at Prof. Dr. R.D. Kandou Hospital.Method: An analytic-cross-sectional study was conducted in gastroenterology clinic of Prof. Dr. R.D. Kandou Hospital between May–June 2021. We included all patients with reflux esophagitis that proven by esophagoduodenoscopy and the severity was graded using Los-Angeles criteria. The GERDQ score was calculated in all patients. The analysis of sleep and life quality was assessed using validated Indonesian version of Pittsburgh-Sleep-Quality-Index (PSQI) and WHO-quality-of-life-BREF (WHOQOLBREF) questionnaire. Independent T-test was used to compare GERDQ, PSQI, WHOQOLBREF score with esophagitis severity degree.Results: Among 30 patients with esophagitis, 70% was male. We found 22 patients with Los-Angeles-grade-A and 8 patients with Los-Angeles-grade-B. The analysis showed no significant different between GERDQ score with esophagitis grade (p = 0.753). There was no association between esophagitis grade with sleep quality (p = 0.125), physical health (p = 0.161), psychological health (p = 0.728), and environmental health (p = 0.133). But we found significant association between esophagitis grade with social relationship life quality (p = 0.028).Conclusion: Patients with higher esophagitis degree had lower social relationship, but not associated with another domain of WHOQOLBREF, sleep quality, and GERDQ score.